Residues of Citrus sinensis (L.) Osbeck as agents that cause a change in antioxidant defense in plants - Patrícia Mayra Pavan Nunes; Cristiane Bezerra da Silva; Cristiane da Silva Paula; Fernanda Ferreira Smolarek; Walmes Marques Zeviani; Suelen Cristina Chaves; Fernando Lorini; Josiane de Fátima Gaspari Dias; Obdulio Gomes Miguel; Sandra Maria Warumby Zanin; Marilis Dallarmi Miguel (Universidade de São Paulo, 2015)
This work aimed to verify the allelopathic potential of the extract of Citrus seeds, for the purpose of adding a sustainable value to the fruit seeds toward their use as industrial residues. The extract was obtained with a Soxhlet apparatus by using hexane, chloroform, and methanol as solvents. The hexane extract of the Citrus seeds primarily consisted of linoleic acid (36.6%), followed by α-linoleic acid (25.3%), oleic acid (17.8%), palmitic acid (9.7%), and estearic acid (3.3%). The analysis results indicate that the oil is similar to those used in the cosmetics and food industries and has an economic value from its industrial application. In addition, the use of the oil causes changes in the oxidant balance, germination, and growth of plants.